Improvement of the Compression-ignition Engine Indicators Using Dual Fuel (Diesel and Liquefied Petroleum Gas). (2016) - Rimkus, Alfredas; Berioza, Modestas; Melaika, Mindaugas; Juknelevičius, Romualdas; Bogdanovičius, Zenonas
Abstract: The influence of additional supplies of liquefied petroleum gas (LPG) blends is investigated on the energetic and environmental indicators of the compression-ignition (CI) engine operating diesel (dual fuel). By performance of the tests and numerical simulations using the AVL BOOST program, it was found that an additional supply of LPG affects the combustion process of combustible mixture and reduces the thermal efficiency of the engine. The change of the composition of the combustible mixture increases incomplete combustion products, that is concentration of carbon monoxide (CO), hydrocarbons (HC) and smoke in the exhaust gases, but reduces nitrogen oxides (NOx) and carbon dioxide (CO2 ) emissions. Using the dual fuel and by optimizing the diesel advanced injection timing, the engine operating efficiency is close to diesel fuel, the concentration of incomplete combustion product decreases, but exceeds the emissions produced by the use of pure diesel.